KINETIC DETERMINATION OF ASCORBIC ACID a WITH SPECTROPHOTOMETRIC DETECTION (Journal of Sciences, Islamic Republic of Iran)
A simple and rapid method has been developed for the determination of ascorbic acid in fruit and pharmaceutical products. The method is based on the measurement of the reaction rate between ammonium molybdate and ascorbic acid in acidic media. The reaction was monitored spectrophotometrically at 800 nm by fixed-time and variable-time methods. The calibration graph was linear in the range of 5 0 ×1 0 - 6.0 ×10 M ascorbic acid when using a fixed-time method. The relative standard deviation for ten replicate analyses is 2.7% for 5.0 × 10 a scorbic acid. The limit of detection is 2.0×10 M. T he effect ofvarious species was studied for this determination.